Money and banking - Fisher, Douglas (Homewood, Ill. : R. D. Irwin, 1971)
In this book, Fisher has attempted to reverse the emphasis by stressing theory and minimizing the descriptions of institutions. The author promises "to bring the powerful tools of microeconomics to bear on a wide range of monetary problems. The book is divided into three parts: the monetary mechanism (chapters 1-9), the capital markets (chapters 10-14), and the open economy (chapters 15-18). A review of the table of contents indicates a number of chapters not typically found in the more traditional books. Fisher includes entire chapters on method, the term structure, portfolio analysis, stock prices, and uncertainty.
Includes bibliographical references and index.
rpm 18/04/2018
Loans
Keywords: Financial economics; Money; Monetary policy; Banks and banking